Deterioration and Microstructural Characterization of Reinforced Concrete Beam Buried in Lagoon and Fresh Waters (Nigerian Journal of Technology, 2021)
The effect of the sulphate attack on reinforced concrete structures in Lagos lagoon environment has become a concern for stakeholders in the construction industry. This study investigated the flexural strength and microstructure of reinforced concrete beams for a period of 365 days. Thirty beams with dimension 150 mm x 150 mm x 600 mm were cast using grade 30 concrete with water cement ratio of 0.45 and cured for 28, 90 and 365 days, in both lagoon and fresh water. Flexural strength and microstructural test were carried out. The result showed that the flexural strength of concrete submerged in fresh and lagoon water were 24.6 and 20.3 N/mm^2 respectively. The microstructure also confirmed the fact that specimens submerged in the lagoon had more defects and deterioration than the sample cured in fresh water at 365 days.http://dx.doi.org/10.4314/njt.v40i2.2